Design Perangkat Sistem Penyiraman Pada Pemantauan dan Penyiraman Tanaman Kopi dan Nutrisi Tanah Otomatis Berdasarkan Suhu, Kelembapan, dan Keasaman Berbasis IoT - Ajisaka, Tito; Hertiana, Sofia Naning; Karna, Nyoman Bogi Aditya (eProceedings of Engineering, 2024)
Indonesia has ideal geographical conditions for coffee cultivation. Topographical variations, tropical climate, altitudinal differences, and soil fertility are factors that favor coffee growth. However, challenges include long dry seasons due to climate change, remote mountainous locations, and many farmers still using traditional methods that are less efficient. This research introduces an automation solution that includes soil moisture detection to adjust watering needs, air temperature and humidity monitoring, and soil pH measurement to maintain optimal coffee plant nutrition. The system consists of various main sensors, such as the ESP32 microcontroller, soil moisture sensor, DHT11 temperature sensor, soil pH sensor, and RS485 sensor to measure soil macro nutrient content such as NPK. The system's energy is supplied by solar panels, with internet provided by MiFi Orbit Star. The data collected by the sensors is sent in real-time to the server, then displayed through a web interface, allowing for more efficient remote monitoring of land conditions. The results prove that the application of IoT technology and integrated sensors provides an innovative solution in improving the productivity and operational efficiency of coffee cultivation. The RS485 NPK sensor showed high accuracy with 99.91% for Nitrogen, 99.70% for Phosphorus, and 99.80% for Potassium compared to analog sensors. The implementation of this system not only reduces the need for manual intervention, but also supports sustainable and environmentally-friendly farming practices. The benefits of this system include improved crop quality, more efficient use of resources, as well as more accurate monitoring of farm conditions. Keywords- Coffee Cultivation, Farm Automation, Internet of Things, RS485 Sensor